2021
DOI: 10.1093/jeg/lbab011
|View full text |Cite
|
Sign up to set email alerts
|

(The Struggle for) Refugee integration into the labour market: evidence from Europe

Abstract: We study the labour market performance of refugees vis-à-vis comparable migrants across 20 European countries and over time. In the first part of our analysis, we document that labour market outcomes for refugees are consistently worse than those for other migrants. Refugees are 11.6% less likely to have a job and 22% more likely to be unemployed than other migrants with similar characteristics. Their income, occupational quality and labour market participation are also relatively weaker. These gaps are larger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 57 publications
2
83
1
Order By: Relevance
“…Empirical studies on the labor market situation of refugees have shown that refugees are generally disadvantaged compared to other migrants in Western destination countries (DeVoretz et al, 2004;Bevelander, 2011;Brücker et al, 2019;Brell et al, 2020;Fasani et al, 2022). Overall, their employment rates are far below those of other foreign population groups and even further below those of the native-born population of the respective host countries (Dustmann et al, 2017;Brell et al, 2020).…”
Section: Refugees' Labor Market Situationmentioning
confidence: 99%
“…Empirical studies on the labor market situation of refugees have shown that refugees are generally disadvantaged compared to other migrants in Western destination countries (DeVoretz et al, 2004;Bevelander, 2011;Brücker et al, 2019;Brell et al, 2020;Fasani et al, 2022). Overall, their employment rates are far below those of other foreign population groups and even further below those of the native-born population of the respective host countries (Dustmann et al, 2017;Brell et al, 2020).…”
Section: Refugees' Labor Market Situationmentioning
confidence: 99%
“…Dispersal policies, by depriving individuals from the possibility to migrate to areas with better economic conditions, may therefore lead to worse outcomes overall. Edin et al (2004) and Fasani et al (2021b) come to that same conclusion by using country variation in changes in dispersal policies, focusing on employment rates. Fasani et al (2021b) investigate dispersal policies where refugees were either allocated according to population size (as in Denmark, the Netherlands and Norway), or according to other non-employment criteria such as social housing opportunities (as in Sweden or the UK).…”
Section: Eckert Et Al (mentioning
confidence: 70%
“…Edin et al (2004) and Fasani et al (2021b) come to that same conclusion by using country variation in changes in dispersal policies, focusing on employment rates. Fasani et al (2021b) investigate dispersal policies where refugees were either allocated according to population size (as in Denmark, the Netherlands and Norway), or according to other non-employment criteria such as social housing opportunities (as in Sweden or the UK). They conclude that dispersal policies or -even worse -policies that allocate refugees according to cost saving considerations (often to deprived areas with low cost housing) denies refugees of opportunity, reducing their employment rate and increasing their welfare dependence.…”
Section: Eckert Et Al (mentioning
confidence: 70%
See 1 more Smart Citation
“…On the one hand, a more homogeneous sample in terms of language skills adds additional robustness to the findings with regard to German-speaking migrants. Because language ability is a key human capital component and main determinant for migrants’ labor market participation [ 76 , 105 ], it is therefore an important element of individual productivity, too, especially in occupations that involve teamwork or customer contact (which is not captured in this questionnaire). A sample with substantial differences in the respondents’ language skills would therefore make the distinction between objective, productivity-related firing grounds and discrimination more difficult.…”
Section: Discussionmentioning
confidence: 99%